Diagnosed hematological malignancies in Bangladesh - a retrospective analysis of over 5000 cases from 10 specialized hospitals - Sorowar Hossain, Mohammad; Iqbal, Mohd S; Ahmed Khan, Mohiuddin; Golam Rabbani, Mohammad; Khatun, Hazera; Munira, Sirajam; Miah, M Morshed Zaman; Kabir, Amin Lutful; Islam, Naima; Farhana Dipta, Tashmim; Rahman, Farzana; Mottalib, Abdul; et al. (© 2014 BioMed Central Ltd., 2017)
This article was published in BMC Cancer [© 2014 BioMed Central Ltd.] and the definite version is available at: http://bmccancer.biomedcentral.com/articles/10.1186/1471-2407-14-438